Clinical predictors for mechanical ventilation assistance in Guillain-Barré syndrome - Rodríguez-Méndez, Axel Abel; Briseño-Ramírez, Jaime; Rivas-Ruvalcaba, Francisco Javier; Solis-Estrada, Javier; Alcázar-García, Liliana Berenice; Díaz-Ramírez, Karely; Lira-Jaime, Gabriela; Sánchez-Román, Edgar Javier; Zúñiga-Ramírez, Carlos (Frontiers in Neurology, 2024)
Background Guillain-Barré syndrome (GBS) frequently leads to respiratory failure and autonomic dysfunction, resulting in approximately one-third of patients requiring mechanical ventilation. Objective This study aimed to identify clinical predictors for mechanical ventilation in patients with GBS. Methods This research was conducted from 2010 to 2021 using registries from a tertiary hospital in an upper middle-income Latin American country. Participants were categorized into two groups based on their ventilation status. Demographic data were collected, and independent predictors of the need for mechanical ventilation were determined through multivariate logistic regression analysis. Results Dysautonomic events occurred in 36% of the patients, with 17% requiring mechanical ventilation; the average duration of intubation was 1.16 ± 3.18 days. The multivariate analysis indicated that bulbar dysfunction significantly increased the likelihood of requiring mechanical ventilation by 19-fold (OR 18.67, 95% CI 5.85–59.42), followed by ophthalmoplegia, which increased the likelihood by sixfold (OR 5.68, 95% CI 1.28–25.19). Conclusion Bulbar dysfunction, dysautonomia, and lower Medical Research Council (MRC) scores were significant predictors of the need for mechanical ventilation in hospitalized GBS patients. These findings support the need for close monitoring and early admission to the intensive care unit (ICU) admission for at-risk patients.